Laypeople's Collaborative Immersive Virtual Reality Design Discourse in Neighborhood Design - Chowdhury, Shuva; Schnabel, Marc Aurel (Frontiers in Robotics and AI, 2019)
The article discusses design communication and participation of laypeople in a virtual participatory urban design process. We speculate that an immersive virtual environment facilitated instrument can allow laypeople to take part actively as designers in the early stage of urban design ideation and generation. We have developed a design communication framework where laypeople can participate in design discourse on a neighbourhood’s future urban form. The strategy describes an urban design intent, which is informed by the development procedure of an instrument and workflow to engage participants. The integration of the instrument and the engagement procedure enable continuous designing of urban forms by laypeople. A protocol analysis has been undertaken to investigate design communication. A coding scheme is applied to investigate, analyse and understand how laypeople communicate with the design instrument and control design in the virtual environment. Through engaging non-experts, the research impacts on the perceptual affordance created through the interaction between virtual 3D buildings, immersive and non-immersive visual information and verbal conversation. We have identified that spontaneous exchange of visual information in a virtually informed environment along with verbal conversation, can produce meaningful design alternatives.